Identifying when it is financially beneficial to increase or decrease fungicide dose as resistance develops - van den Bosch, F.; Lopez-Ruiz, Fran; Oliver, Richard; Paveley, N.; Helps, J.; van den Berg, F. (Wiley-Blackwell, 2018)
When fungicide efficacy declines due to the development of resistance in the pathogen population, growers have to either change to an alternative mode of action or adjust their treatment programme. Adjustments may include either decreasing (or stopping) use of the mode of action, or increasing the total dose applied (by increasing number of applications and/or dose per application, where permitted) to try to maintain effective disease control. This study explores the circumstances under which increasing/decreasing total applied fungicide is financially optimal. A model based on field data is used to optimize the dose of fungicide applied when fungicide resistance develops in a pathogen population. The model is used to explore contrasting pathosystems and fungicide classes. When qualitative fungicide resistance develops, the shape of the disease–yield loss relationship determines whether the optimal total dose increases or decreases with increasing frequency of resistance in the pathogen population. When quantitative fungicide resistance develops, such that effective control can still be obtained with doses close to the maximum permitted dose, the optimal dose increases with increasing frequency of resistance in the pathogen population.